Finite Element Simulation of Cylinder Closure Spinning - Sui, Liyan; Xie, Yilian; Liu, Baoming; Jia, Zhen (Manufacturing Technology Journal, 2023)
As a gas storage container, gas cylinders have been widely used in industry, mining, military, medicine, diving, automobiles and other fields. The gas cylinder produced by spinning can fundamentally eliminate the defects related to the weld in the traditional production process. In order to explore the metal flow law of cylinder closure spinning, its finite element simulation is established and carried out by using ABAQUS/explicit software. The influence of the parameters such as angle radius R and screw wheel installation angle on the metal flow field and wall thickness distribution are studied and revealed.
Keywords: Cylinder closure spinning; Tube blank; Finite element simulation; Metal flow; Wall thickness distribution